Solubility measurement and thermodynamic functions of dehydroepiandrosterone acetate in different solvents at evaluated temperatures. (June 2016) - Cheng, Chao; Cong, Yang; Meng, Long; wang, Jian; Yao, GanBing; Zhao, Hongkun
Highlights: Solubility were determined for dehydroepiandrosterone acetate in nine solvents. Solubility were correlated with four thermodynamic models. Apparent standard enthalpy and excess enthalpy of solutions were evaluated. Abstract: The solubility was measured for dehydroepiandrosterone acetate in cyclohexane, acetone, ethyl acetate, acetonitrile, methanol, 1-butanol, ethanol and isopropanol by high-performance liquid chromatography analysis under the pressure of 101.3 kPa. The temperature of the determination varied from (273.15 K to 318.15) K. The dehydroepiandrosterone acetate solubility increased with the increase in temperature, and obeyed the following order from high to low: ethyl acetate > acetone > 1-butanol > acetonitrile > (cyclohexane, isopropanol) > ethanol > methanol. They were correlated with four models, viz . the modified Apelblat equation, λh equation, Wilson model and NRTL model. The largest average standard deviation is 5.93 × 10 −4, and the largest relative average deviation is 1.18% for each set of solubility values. The calculated solubility was in good agreement with the experimental values for the four models. Moreover, the thermodynamic properties of the solution process, including the apparent standard dissolution enthalpy and excess enthalpy were calculated. The experimental solubility, thermodynamic models and thermodynamic properties are very important in the purification process of dehydroepiandrosterone acetate.